THE RELATIONSHIP OF TOOTH BRUSHING BEHAVIOR, DIETARY PATTERNS, ECONOMIC STATUS ON CARIES OF SOUTH DAHA POPULATION - Maulida Arifa Yasmin; Raden Harry Dharmawan Setyawardhana; Agung Satria Wardhana (Dentin, 2023)
Background: Based on Riskesdas 2018, prevalence of caries between age of 55-64 is 96,8%. The DMT-T index in Samuda Village, South Daha is 8,2. Caries is the destruction of hard surface of the teeth caused by multifactorial etiology, such as host, substrate, time, microorganisms and predisposing factors like tooth brushing behavior, dietary patterns and economic status. Objectives: Analyzed the relationship between tooth brushing behavior, dietary patterns, economic status and dental caries of South Daha population. Methods: This study was an observational analytic research with cross sectional research design. The population was 2,559 people of South Daha aged between 55-64 and 108 people was involved in this study based on simple random sampling technique. Results: Correlation test result, using Somers'd test to analyze the relationship between tooth brushing behavior and dental caries, is 0.000 (p <0.050), which means there is a relationship between tooth brushing behavior and dental caries with correlation strength is 0.582 (moderate). The correlation result between dietary patterns and dental caries is 0.000 (p <0.050) with correlation strength is 0.239 (weak), which means there is a weak relationship between dietary patterns and dental caries. The correlation between economic status and dental caries is 0.000 (p <0.050) with correlation strength is 0.353 (weak), which means there is a weak relationship between economic status and caries. Conclusion: There is a relationship between tooth brushing behavior and dental caries, there is a relationship between dietary patterns and dental caries and there is a relationship between economic status and dental caries. Keywords: Caries, dietary patterns, economic status, tooth brushing behavior,